The influence of different joining processes on mechanical performance of carbon fiber/polyamide (CF/PA6) composites - Hassan, Elwathig Abd all Mohamed; H. H. Elagib, Tienah; Omer Bashier, Ezelarab; E. A. Elabid, Amel.; Zhu, Shu (Gezira Journal of Engineering and Applied Sciences, 2022)
Carbon fiber (CF) reinforced polyamide (PA6) composite materials are broadly used as structural materials in the automotive and aerospace industries due to their distinguished properties. However, due to requirements for the structural integrity of composite materials, there are still limitations in connection of the actual production of CF/PA6 composite. Strong joints of CF/PA6 laminates are highly required for the lightweight design in many fields. Aiming at making comparisons, different processing methods such as adhesive bonding and thermal jointing to form single lap joints between the two CF/PA6 composite laminates are studied. The influences of different processing methods and parameters on the shear strength of joints were also studied. Results showed that conventional adhesive bonding is quite easy to handle and may form rather stronger connections. Thermal joining based on electrical conductors of CF can be used to form a thermoplastic flexible joint design. Thermal joints by hot pressing can further increase the connection strength; when formed by hot pressing under optimum conditions of 250 °C and 2.5MPa, the joint has a shearing strength of 138.85 MPa. It is consequently confirmed that a strong joint of CF/PA6 composite parts could be obtained by thermal joints via the hot pressing process.